2018
DOI: 10.1016/j.drugalcdep.2018.07.041
|View full text |Cite
|
Sign up to set email alerts
|

Usage of low dead space syringes and association with hepatitis C prevalence amongst people who inject drugs in the UK

Abstract: People who inject into their groin were less likely to use LDSS. Exclusive LDSS use was associated with lower prevalence of HCV amongst PWID that started injecting recently, suggesting LDSS use is protective against HCV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 29 publications
0
10
0
1
Order By: Relevance
“…Laboratory studies have shown that LDSS retain less viable HCV in the syringe in subsequent injections than HDSS [8,10], while modelling [11,12] has shown that smaller quantities of blood are transferred with LDSS than HDSS. Limited epidemiological studies also suggest lower HIV and HCV prevalence rates among PWID that use LDSS [13][14][15][16], although these studies have not measured incident infection and only one UK study adequately controlled for other factors that could affect infection risk [13].…”
Section: Introductionmentioning
confidence: 99%
“…Laboratory studies have shown that LDSS retain less viable HCV in the syringe in subsequent injections than HDSS [8,10], while modelling [11,12] has shown that smaller quantities of blood are transferred with LDSS than HDSS. Limited epidemiological studies also suggest lower HIV and HCV prevalence rates among PWID that use LDSS [13][14][15][16], although these studies have not measured incident infection and only one UK study adequately controlled for other factors that could affect infection risk [13].…”
Section: Introductionmentioning
confidence: 99%
“…This research forms part of a multi-disciplinary body of evidence supporting the roll-out of LDSS. In addition, we have previously demonstrated that LDSS use is associated with reduced HCV risk in the United Kingdom, have shown why some PWID use LDSS and some do not [3] and critically shown that NSPs in general are a highly cost-effective way of reducing the spread of HCV among PWID [4].…”
mentioning
confidence: 98%
“…It was encouraging to read Hancock et al's economic analysis of detachable low dead space syringes (LDSS), which concluded that the syringes are cost-saving and lead to additional quality-adjusted life years (QALY) in relation to hepatitis C (HCV) transmission and disease progression [1]. This is a useful addition to the growing body of evidence indicating the acceptability of LDSS among people who inject drugs (PWID) although, as Hancock et al acknowledge, further epidemiological evidence is needed to demonstrate their effectiveness in reducing HCV/HIV acquisition at a population level [2][3][4].…”
mentioning
confidence: 99%
“…Women who inject drugs are at increased risk of HIV/HCV acquisition, violence and poorer mental health compared to their male counterparts, but they also face barriers to services related to stigma, concerns about confidentiality, loss of child custody and gendered power imbalances in injecting relationships [14][15][16]. People who inject crack cocaine are also at increased risk of HIV and HCV acquisition and are less likely to use LDSS [3,5,12]. Services need to adapt to reach these underserved populations, distributing injecting equipment via secondary distribution through peer-led outreach and in homeless hostels.…”
mentioning
confidence: 99%
See 1 more Smart Citation